Application of Hydrogen Peroxide as an Environmental Stress Indicator for Vegetation Management. (October 2018) - Asaeda, Takashi; Jayasanka, Senavirathna Mudalige Don Hiranya; Xia, Li-Ping; Barnuevo, Abner
Abstract: Adaptive vegetation management is time-consuming and requires long-term colony monitoring to obtain reliable results. Although vegetation management has been widely adopted, the only method existing at present for evaluating the habitat conditions under management involves observations over a long period of time. The presence of reactive oxygen species (ROS) has long been used as an indicator of environmental stress in plants, and has recently been intensely studied. Among such ROS, hydrogen peroxide (H2 O2 ) is relatively stable, and can be conveniently and accurately quantified. Thus, the quantification of plant H2 O2 could be applied as a stress indicator for riparian and aquatic vegetation management approaches while evaluating the conditions of a plant species within a habitat. This study presents an approach for elucidating the applicability of H2 O2 as a quantitative indicator of environmental stresses on plants, particularly for vegetation management. Submerged macrophytes and riparian species were studied under laboratory and field conditions (Lake Shinji, Saba River, Eno River, and Hii River in Japan) for H2 O2 formation under various stress conditions. The results suggest that H2 O2 can be conveniently applied as a stress indicator in environmental management.